Paylater as The Millennial Payment: Theory Planned Behavior - Susan Fatmawati; Eko Suwardi (Institute of Research and Community Outreach - Petra Christian University, 2024)
This study aims to identify the motivations of Millennials who use Paylater services as a payment method in transactions and then investigates their perceptions and financial control regarding the risk of Paylater through the theory of planned behavior. This research involves individuals from the Millennial generation who have used Paylater services, using a qualitative approach through interviews. Primary data in the form of interviews in this study uses thematic analysis, by collecting and analyzing data, coding data, developing analytical ideas and concepts, and connecting analysis with the theory used. The results revealed that the ease of access, flexibility, and promo incentives of Paylater motivate Millennials to use it. Social pressure from relatives, the environment, and social media influences this motivation, along with their belief in their control over Paylater. However, Millennials also perceive risks such as spontaneous purchases, financial difficulties, and default, which raises doubts about using this service. These findings highlight the importance of considering psychological aspects, financial literacy, and financial behavior in using Paylater responsibly.